Revision des Genus Anisoplia Serville (1825) (Coleoptera: Lamellicornia, Melolonthidae, Rutelinae). I. Teil. - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
In the first chapters there are discussed the general characters of the genus Anisoplia Serville and if necessary with remarks on the differences to the other genera of Anomalina. There are described as new Anisoplia libanensis n. sp., An. gracilis n. sp., An. cu-prina n. sp., and An. aegyptica n. sp. (all belonging to the Anisoplia segetum-group). Anisoplia segetum itself represents a group of races ("Rassenkreis") consisting of the races: Anisoplia segetum segetum (Herbst), An. segetum croatica n. ssp., An. segetum balcanicola n. ssp., An. segetum pirina n. ssp., An. segetum velutina Erichson, An. segetum zoubkovi Kryn., An. segetum cordofana Burm., and An. segetum griseovillosa Balt. A special chapter deals with the phylogeny of Anisoplia segetum-group. According to the structures of male genitalia (forceps) the group consists of two morphological lines, each of them representing a special line of phylogenetic development. By means of the proceeding differentiation of the forceps structures the species may be so arranged that each of them appears as a further development of the proceeding one.Nomenclatural Actsaegyptica Machatschke, 1961 (Anisoplia), spec. n.cuprina Machatschke, 1961 (Anisoplia), spec. n.gracilis Machatschke, 1961 (Anisoplia), spec. n.libanensis Machatschke, 1961 (Anisoplia), spec. n.balcanicola Machatschke, 1961 (Anisoplia segetum), sspec. n.croatica Machatschke, 1961 (Anisoplia segetum), sspec. n.pirina Machatschke, 1961 (Anisoplia segetum), sspec. n.